Soil Erosion and Deposition Processes of Loess Slopes in Loess Hilly and Gully Region - Liu Ran; Yu Xinxiao; Cai Qiangguo; Sun Liying; Fang Haiyan; Jia Guodong; He Jijun (Shuitu baochi tongbao)
[Objective] The erosion-deposition process of loess slopes under the effects of various influencing factors was studied in order to provide a scientific basis for the rational layout of soil and water conservation measures, and for planning to control and prevent soil and water loss in the loess hilly and gully region of Northern Shaanxi Province. [Methods] The characteristics of erosion-deposition processes on a loess slope under different slope gradients, slope lengths, and 60 mm/h rainfall intensity were studied using an indoor artificial rainfall simulation experiment. [Results] ①The net erosion process mainly occurred before and after reaching the peak value of erosion rate. The erosion rates alternated between positive and negative values during the entire rainfall period, and the erosion process coexisted with the deposition process. ② When the slope was 5°, 10°, and 15°, the erosion per unit area decreased with increasing slope length. There was an obvious deposition process and critical erosion slope length in the 5—10 m slope section. Under the test conditions, the critical slope length of loess slope deposition was in the range of 4—5 m and 5—10 m. ③ Under the gradient of 5° and 15°, during the entire rainfall process, the cumulative erosion per unit area of the 0—5 m slope section was greater than erosion of the 0—10 m slope section, and there was always deposition in the erosion process. On the 10° slope, deposition began to occur about 15 minutes after rainfall. [Conclusion] Slope gradient and slope length are important factors affecting erosion-deposition processes of a loess slope. The sediment concentration of slope runoff and erosion per unit area can be used as important factors to characterize the erosion-deposition characteristics of a loess slope. To control soil and water loss on a slope, soil and water conservation measures that intercept runoff at the middle and upper slope positions should be adopted.